THE TRANSFORMATION OF SHAKESPEAREAN PLOTS FOR UZBEK AUDIENCES - Sharipova Makhfirat Bozor kizi (Western European Studies, 2025)
This article examines how the narrative structures of Shakespeare’s plays undergo transformation when adapted for Uzbek audiences. Cultural interpretation, theatrical conventions, and audience expectations influence decisions related to plot compression, character reinterpretation, and thematic emphasis. By analyzing selected Uzbek performances, the study identifies contextual substitutions, symbolic modification, and dramaturgical restructuring as key adaptation strategies. The results demonstrate that transformations do not diminish Shakespeare’s relevance; instead, they reinforce cultural accessibility and theatrical resonance within the Uzbek context
Keywords: Plot adaptation; dramaturgy; cultural context